2011
DOI: 10.1038/nature10708
|View full text |Cite
|
Sign up to set email alerts
|

DCC constrains tumour progression via its dependence receptor activity

Abstract: The role of deleted in colorectal carcinoma (DCC) as a tumour suppressor has been a matter of debate for the past 15 years. DCC gene expression is lost or markedly reduced in the majority of advanced colorectal cancers and, by functioning as a dependence receptor, DCC has been shown to induce apoptosis unless engaged by its ligand, netrin-1 (ref. 2). However, so far no animal model has supported the view that the DCC loss-of-function is causally implicated as predisposing to aggressive cancer development. To i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(111 citation statements)
references
References 18 publications
4
105
0
2
Order By: Relevance
“…37 Dcc mutations are found in~2.5% of COSMIC samples compared with~0.5% for krm1. However, since dcc is a gene three times longer than krm1, and therefore more likely to accumulate mutations, the frequency of krm1 mutations in cancers appears comparable to that of dcc.…”
Section: Discussionmentioning
confidence: 95%
“…37 Dcc mutations are found in~2.5% of COSMIC samples compared with~0.5% for krm1. However, since dcc is a gene three times longer than krm1, and therefore more likely to accumulate mutations, the frequency of krm1 mutations in cancers appears comparable to that of dcc.…”
Section: Discussionmentioning
confidence: 95%
“…Both DCC and UNC5C have been suggested to be colon cancer tumor suppressors because their expression is lost or markedly decreased in the vast majority of colorectal cancers (17)(18)(19)(20). Moreover, inactivation of UNC5C or specific inactivation of DCC's proapoptotic activity in mice was shown to promote intestinal tumor progression (20,21). Moreover, it was recently shown that missense mutations in UNC5C are associated with risk of familial colorectal cancer (22).…”
mentioning
confidence: 99%
“…DCC je tumor supresorový gen, ačkoliv o jeho jasném zařazení se vedou stále velké diskuze. Někdy je označován jako poslední obránce (Late Gate keeper), který limituje progresi tumoru navozením apoptózy [46]. Jeho funkcí je blokovat růst buňky v případě absence svého ligandu (netrin-1).…”
Section: DCCunclassified